Post-harvest characterization of the hazelnut sector - Ana Cristina Ferrão; Raquel Guiné; Margarida Rodrigues; Rui Droga; Paula Correia (Instituto Politécnico de Viseu, 2020)
Introduction: Hazelnut is one of the most consumed nuts in the world, and its consumption is associated with numerous health benefits. Objectives: This study aimed to analyse the post-harvest practices in the hazelnut sector in a sample of Portuguese producers living in the Viseu district and also in the unique Portuguese industry in this sector. Methods: It was undertaken a descriptive cross-sectional study on a sample consisting of 11 participants (10 hazelnut producers and one hazelnut industry in Portugal). The surveys were applied by personal interview after informed consent only to adults (aged 18 or over). Results: The results obtained showed that 80.0% had their hazelnut plantation in the form of an orchard, with areas under 10 hectares, and in most cases aged 20 years or more. The main varieties used by the producers were Grada de Viseu and Segorbe. For the industry, the main varieties were Grada de Viseu, Ennis and Tonda de Giffoni. For the majority of participants (87.5%), the harvest was done manually, with the fruits being stored in warehouses at room temperature and without relative humidity control. In the case of industry, hazelnut kernels were stored at a controlled temperature (0-10 ⁰C) and with relative humidity control (<70%). The material used for transport/sale was different for industry and producers. Conclusions: This study clarified the post-harvest practices, as well as some of the difficulties experienced by hazelnut producers in Portugal.